Post-Capitalist Imaginaries: The Case of Workers’ Collectives in Greece - Kokkinidis, George (My University, 2015)
This article focuses on the case of two workers’ collectives in Athens, Greece, and reflects on the transformative potential of entrepreneurial creation. I argue that these social and economic experiments are collective and essentially political. Thus, breaking from the individualism that characterizes entrepreneurial discourse, this article looks at the collective dimension of entrepreneurial activity, and by reflecting on the collective capacities and transformative potential of these social initiatives, in terms of creating shared forms of sociality and bringing forward new ways of living and collective co-existence, it points to the inherently political character of entrepreneurship.
Keywords: direct democracy; self-management; horizontality; public entrepreneurship; prefiguration; post-capitalist imaginaries